Membrane technology: Ultrafiltration (2018)
Membrane Techno logies MT has a great impact on the development of new and better products, on the conservation of the environment, on the paint industry and medicine, among others. In the food industry MT are applied in a variety of areas, for example, in seawater desalination, wastewater treatment and juice clarifi cation. In the case  of dairy products, it has been used in the production of new derivatives, as in the case of whey proteins or lactose. In the present review, the use of Ultrafi ltration (UF) was studied. A special emphasis is placed on the dairy industry, which outlines the growing boom of MT, thanks to the fact that it allows the retention and separation of particles, is environmentally friendly and allows the development of new foods. Finally, it is essential to continue searching for alternatives to control the clogging of the membranes, extending the useful life of these materials, since it is the phenomenon that aff ects them the most.